Carcass, organ and organoleptic characteristics of broilers fed yeast treated raw soya bean and full fat soya bean - J. Onwumelu, I.; J. Akpodiete, O.; C. Okonkwo, J. (Scientific Journal of Zoology, 2014)
Carcass, Organs andOrganoleptic Characteristics of broilers fed yeast treated raw soya bean (RSB)and full fat soya bean (FFSB) were studied using one hundred and eighty day oldchicks. Standard poultry management techniques were applied and experimenteddiets provided ad libitum. Fifteen diets consisting of various proportions ofFFSB, RSB and yeast were formulated for the starter phase (0- 28 days) andfinisher phase (29-56 days), respectively. The diets in each phase wereformulated to be isocaloric and isonitrogenous with the starter dietscontaining approximately 2900 kcal/kg ME and 23% crude protein, and thefinisher diets containing approximately 3000 kcal/kg and 20% crude protein. Thecarcass and organs studied include weights after defeathering, cut- up partswhich include thighs drumstick, shanks, wings, neck, back, breast head, andorgans such as heart, liver, spleen and gizzard. The lengths of theproventriculus, small intestine, colon and caeca were also measured. The studyshowed that RSB at the levels fed with and without yeast inclusion had nolethal effect on broiler chickens. However, higher performance may be achievedwhen RSB is fed at 25 % with 6 g/kg yeast inclusion at starter phase and at 25% without yeast or 75 % with 12 g/kg yeast inclusion. The study therefore,further maintained that inclusion of RSB with or without yeast in the diets ofbroilers can equally produce broiler with good weight comparable with feedingFFSB or conventional diets; feeding 75 % FFSB + 25 % RSB without yeastinclusion is capable of increasing the proportion of the broilers’ head andshank; RSB inclusion in broiler diets cause increase in the weight of thegizzard, pancreas as well as on the abdominal fat, and feeding FFSB and RSBwith or without east inclusion do not exert any noticeable effect on theorganoleptic ualities tenderness, flavour and in general acceptability) ofbroilers. However, RSB enhances the juiciness of broilers.